Day of remembrance of the holocaust and of prevention of crimes against humanity : 2nd seminar of ministers of education, Cracow and Auschwitz-Birkenau (Poland), 4-6 May 2005 : proceedings = Journée de la mémoire de l’holocauste et de la prévention des crimes contre l’humanité : 2e séminaire des ministres de l’education, Cracovie et Auschwitz-Birkenau (Pologne), 4-6 Mai 2005 : actes. ([Strasbourg])
222 s.